Modern high school handbook: analysis of sexism and gender stereotype - О. Melnychenko (Borys Grinchenko Kyiv Metropolitan University, 2024)
The article is focusing on one of the most important problems of gender studies - the creation of modern methodological and curricular support for the educational process in higher education. The author analyses the experience of teaching the elective course 'Gender Studies' for Bachelor's students majoring in Primary Education at the Faculty of Pedagogical Education of Borys Grinchenko Kyiv Metropolitan University. This course is practice-based and aims to prepare pre-service teachers to address gender issues in the educational process. Teaching this course raised questions about the content of higher education textbooks and their analysis concerning sexism and gender stereotypes. The author recognizes that textbooks on gender issues are currently linked to certain courses: gender psychology, gender sociology, gender pedagogy, gender journalism, etc. However, according to the author, a modern textbook should be comprehensive and based on the latest scientific research, deep interdisciplinary connections, and contemporary practice. The article defines the main characteristics of a modern textbook in general and gender studies, in particular: it should be comprehensive in terms of analysis when it comes to sexism and gender stereotypes, regardless of the specialty; the content of any textbook should be based on scholarly research in the field of gender studies; the textbook should show deep interdisciplinary connections; the formation of critical thinking of students is the main goal of any modern textbook, regardless of the specialty it is written for; without the use of interactive teaching methods, it is impossible to create a modern textbook. The article also discusses approaches and methods for analyzing textbooks for sexism and gender stereotypes. The author pays special attention to hidden discrimination in the curricula on gender equality of students and schoolchildren